ANALISIS PENGEMBANGAN WILAYAH PETERNAKAN SAPI POTONG DI KABUPATEN SUBANG - Ferdi Fathurohman (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
This research aims to analyze the development potential of the regions of beef cattle and the factors that influence the development of beef cattle in the Regency of Subang. Research carried out by analyzing the primary data from a breeder and secondary data are sourced from the Department of animal husbandry and animal health District of Subang, food security and animal husbandry Office of West Java province and the Central Bureau of statistics the Regency of Subang. The data are analyzed in a descriptive and statistical. Analysis of the potential of the region using the parameters of location quotient (LQ) and factors development of beef cattle were analyzed by linear regression model, with multiple dependent factor (Y) beef cattle Population and the independent variable (X) from the a row is beef cattle population total population of Subang, County, and sales of beef cattle out of the Kabupaten Subang. Keywords: Potential, Region, Beef Cattle